Technology Incubators as Nodes in Knowledge Networks - Danny Soetanto; Marina Van Geenhuizen (European Regional Science Association (ERSA), 2005)
It is widely accepted that new knowledge underpinned innovation and growth influences economic activities. Economic agents rely not only on their own knowledge but also knowledge from others, whether it be codified and 'transferred via ICT' or in tacit form. Moreover, it has long been argued that the acquisition of latter type of knowledge is influenced by geographic proximity. Based on this argument, it follows that the part firms' supply of knowledge depends on how close, in terms of physical distance, to other firms, suppliers, customers, and research institutions, they are located. They are all can be categorize as a pool of knowledge that important for the firms' growth and innovation capacity. Today, we witness many initiatives from policy makers around the world to compete in an increasingly technology- driven global economy through the establishing of technology incubators. Technology incubators can be conceived as organizations and/or facilities to enhance high-technology firm establishment and survival. Mostly they are located near the university or research center. There are many success stories on the contribution of incubators to the regional growth. At the same time, technology incubators have been widely criticized in the academic literature when judged in terms of regional innovation and knowledge development. The critics include the relying on an outdated, linear, model of innovation, which assumes that knowledge can be transferred directly from university to firms. However, innovation is now widely recognized as a complex non-linear process involving feedback loops and the creation of synergies through a diverse range of knowledge networks. Therefore, our understanding about knowledge spillover processes connected with incubator is yet poor. Very little is known about the mechanisms of knowledge exchange and spillover initiated by incubator and their role in supporting the growth of the firm. In this study we draw on the current body of literature, mainly agglomeration theories, and use the concepts of tacit knowledge and context to understand how knowledge spillovers actually take place. Our objective is to build a conceptual framework that describes how technology incubators operate as a mediator of knowledge for their tenants. In addition, based on empirical data of high-technology start-ups at TU Delft (The Netherlands), this study tests the proposition that not only geographic proximity to the university, but also that relations with other firms, particularly customers and suppliers matters. We also consider the function of ICT in shaping the new role of technology incubators in providing knowledge support. By explicitly analyzing the knowledge spillovers and mediation role offered by technology incubators, we seek to open up the 'black box' of the incubation process as a source of learning and gaining knowledge resources. We conclude the paper with a few recommendations for policymaking and further research.
Keywords: 330